THE PLACE OF INTERNET TECHNOLOGIES IN THE MODERN EDUCATIONAL SYSTEM (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the role of internet technologies in the modern education system, their opportunities, and the emerging problems. It examines the use of internet resources in the educational process to enhance independent thinking, critical approach, digital literacy, and creative potential of students. The negative consequences of improper and uncontrolled use of these technologies are also discussed.